Green and Safe “By Design”: A Conceptual Tool to Avoid Hazardous Substances in Early Phases of Product Development - Rocco, Claudio (International Journal of Integrated Engineering, 2023)
Sustainability has to be managed in order to guarantee health, social equity, resource optimization and economic activities and this awareness is grown considerably. At the same time, this consciousness leads us to consider sustainability also as a social and a business driver on the economic side and a great opportunity by an environmental point of view. Further, according to several regulations, producers are responsible of their devices in terms of environmental pollution, from production and market launch to disposal activities when they become unusable. This fact changes the role of designers, which becomes wider in a multidisciplinary context. For this reason, this paper proposes an approach that supports designers during the development of more sustainable products with the aim to reduce the amount of hazardous substances (according to European RoHS regulations) and it allows firms and academic R&D departments to reduce risks of a missing compliance. The approach is structured according to a flowchart that addresses designers to more suitable product solutions in terms of environmental impact. The methodology applied to the case studies, in fact, show that an early assessment in first design phases allows developers to have safer and more sustainable product prototypes and its application can be proposed also during design courses in an educational context.